ENHANCING COMMUNICATIVE COMPETENCIES IN ENGLISH LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the importance of developing communicative competence in English lessons. The author analyzes the structure of lessons and methods that contribute to the effective development of this key skill. The main idea of the article is that an emphasis on communicative skills from the very beginning of learning contributes to the rapid and high-quality acquisition of a foreign language. In the context of modern education, the article emphasizes the importance of actively involving students in communication in English with the help of various games and modern technologies, which contributes not only to the improvement of language skills, but also to the development of general communicative skills.